PENGARUH LINGKUNGAN KERJA, KOMPENSASI, DAN MOTIVASI TERHADAP KINERJA PEGAWAI NEGERI SIPIL DI RUMAH SAKIT DAERAH MADANI PROPINSI SULAWESI TENGAH - Prayogo Mukti, Try (Katalogis, 2015)
This research aims to: (1) know and analyze the effects of environment, environment, compensation, and motivation on employees’ performance in Madani Regional Hospital of Central Sulawesi Province. ,(2) know and analyze the effects of environment on employees’ performance in Madani Regional Hospital of Central Sulawesi Province; ,(3) know and analyze the effects of compensation on employees’ performance in Madani Regional Hospital of Central Sulawesi Province; ,(2) know and analyze the effects of motivation on employees’ performance in Madani Regional Hospital of Central Sulawesi Province. This is a descriptive and causal research involving 180 employees as the sample which has been determined using proportional random samping method method. To collect data, this research employs means of questionnaire and multiple linear regression as analysis method. The result show that : 1) environment, compensation, and motivation simultaneously have positive and significant effects on employees’ performance in Madani Regional Hospital of Central Sulawesi Province; 2) environment positively and significantly has partial effect on employees’ performance in Madani Regional Hospital of Central Sulawesi Province; 3) compensation positively and significantly has partial effect on employees’ performance in Madani Regional Hospital of Central Sulawesi Province; 4) motivation positively and significantly has partial effect on employees’ performance in Madani Regional Hospital of Central Sulawesi Province.